2022
DOI: 10.3390/jfmk7010017
|View full text |Cite
|
Sign up to set email alerts
|

Drop Jumping on Sand Is Characterized by Lower Power, Higher Rate of Force Development and Larger Knee Joint Range of Motion

Abstract: Plyometric training on sand is suggested to result in advanced performance in vertical jumping. However, limited information exists concerning the biomechanics of drop jumps (DJ) on sand. The purpose of the study was to compare the biomechanical parameters of DJs executed on rigid (RIGID) and sand (SAND) surface. Sixteen high level male beach-volleyball players executed DJ from 40 cm on RIGID and SAND. Force- and video-recordings were analyzed to extract the kinetic and kinematic parameters of the DJ. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 66 publications
(124 reference statements)
1
19
1
Order By: Relevance
“…As already mentioned, training for sports performed on compliant surface (e.g., sand for beach volley) may benefit from matching the surface stiffness (53). Although few studies have investigated the differences in biomechanical adaptations between plyometric training performed on rigid and compliant surfaces (52), they have all indicated that jump-related performances can be increased after training on both surfaces (78)(79)(80). For example, the study by Ahmadi et al (79) found that an 8-week plyometric program in women volleyball players increased drop jump height to a greater extent when the training exercises were done on a rigid surface than on sand, but the opposite was observed for the CMJ.…”
Section: Type Of Ground Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, training for sports performed on compliant surface (e.g., sand for beach volley) may benefit from matching the surface stiffness (53). Although few studies have investigated the differences in biomechanical adaptations between plyometric training performed on rigid and compliant surfaces (52), they have all indicated that jump-related performances can be increased after training on both surfaces (78)(79)(80). For example, the study by Ahmadi et al (79) found that an 8-week plyometric program in women volleyball players increased drop jump height to a greater extent when the training exercises were done on a rigid surface than on sand, but the opposite was observed for the CMJ.…”
Section: Type Of Ground Surfacementioning
confidence: 99%
“…The ground surface (athletic track, rubber floor, sprung surface, grass, and sand) may further influence jumping performance. It recently was reported that drop jumps from 40 cm onto sand, for example, reduce jump height (~20%), vertical reaction force, and power output but increase RFD, work, knee joint range of motion, and peak ankle angular velocity during the downward phase (52). Due to the greater compliance of sand relative to a rigid surface, it can provide injury prevention under demands for large energy expenditure (53).…”
Section: Characteristics Of Plyometric Exercisesmentioning
confidence: 99%
“…The analysis of the recorded time curves provided the following parameters [7,36,39,40] using the modules of the K-Dynami (©: Iraklis A. Kollias) software:…”
Section: Data Analysis 251 Kinematic and Kinetic Parameters Derived F...mentioning
confidence: 99%
“…A vast amount of information on the decreased h JUMP on sand (SJS) compared to a rigid (RJS) jumping surface exists in the literature for BV players [ 2 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The decreased h JUMP on a SJS compared to RJS is associated with a lower force and power outputs [ 2 , 17 , 18 , 19 ] due to the less stiff surface and larger friction compared to indoor sport surfaces [ 15 ]. This deprives practitioners of applying force fast during the jumping tests, resulting in a lower power output and eventually poor jumping performance [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%